Manian Tradition: History, Social, and Economy of Kailolo Village, Central Maluku, East Indonesia - M. Syafin Soulisa; Andi Ismail Marasabessy (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This research aims to find out the history, process, and impact of the implementation of Manian tradition in Kailolo Village, Central Maluku, Eastern Indonesia. The novelty of this research is to examine the cultural history, and its impact on the social life of the community and the income of the people of Kailolo Village. This research was conducted using an ethnographic approach with interview, observation, and documentation data collection techniques. The results of the study show that this Manian tradition has been carried out since ancient times where this tradition was carried out to commemorate the birthday of the Prophet Muhammad SAW. Manian implementation has rules which must be started by the Tuanany clan, the Marasabessy Putiiman clan on the 25th Rabiul Awal, the Usemahu clan on the 26th Robi’ul Awal, the Marasabessy Nurlembe clan on the 27th Rabi'ul Awal, the Ohorella clan on the last Monday of the month of Robi’ul Awal, and the Marasabessy Nurlembe Minor clan must be after the Marasabessy Nurlembe clan. The implementation of Manian greatly impacted the solidarity and brotherhood of the people of Kailolo village. In addition, the Manian celebration also affects increasing the income of speedboat business actors, motorcycle taxi drivers, and small traders.